Survival and prognostic factors of oral cancer patients in Hospital Universiti Sains Malaysia, Kelantan - Asmani, Abd. Razak (2008)
Survival and prognostic factors of oral cancer in Hospital Universiti Sains Malaysia, Kelantan Introduction: Oral cancer is a preventable disease that gives high impact on mortality and morbidity as well as patients' quality of live. Worldwide, the five-year survival rate remained unchanged despite the advancement in the technology in diagnosis and treatment of oral cancer, as well as the highly experience specialist. The aims of this study were to determine the survival and to identify the prognostic factors that influence the risk of death of oral cancer patients in Hospital Universiti Sains Malaysia (HUSM). Methodology: A retrospective record review was conducted from August to December 2006 in HUSM involving 133 patients diagnosed as oral cancer from 1986 to 2005. Additional followup of one year after the recruitment of the subjects was done from 151 January till 31 51 December 2006 to verify patients' status. All patients who fulfilled the inclusion criteria were included in the study. The required information at time of diagnosis as well as patients' survival status until 31st December 2006 was retrieved from medical records by the principle researcher and transferred to a specially design data extraction form. For some patients who were alive upon discharged from hospital but defaulted appointment or were loss to follow up, telephone calls and home visit were conducted XV Ill to obtain information on patients' survival status. Data entry and analysis was done using SPSS version 12 and STATA version 8. Kaplan-Meier was used to calculate survival estimates while Cox Proportional Hazards Model was used to determine prognostic factors. Results: The overall 5-year survival rate for oral cancer patients m HUSM was 19.6% (95%CI:12.9, 27.2) with median survival time of 10 months. Adjusted for other variables, Cox Proportional Hazards Model identified the significant prognostic factors that influence death in oral cancer patients in HUSM as age at diagnosis (HR=l.02; 95%CI=l.00-1.03; p=0.004), sex (HR=0.61; 95%CI=0.40-0.95; p=0.028), weight loss (HR=1.74; 95%CI=1.13-2.64; p=O.Ol2), pain (HR=1.64; 95%CI=l.Ol-2.66; p=0.045), earache (HR=2.55; 95%CI=1.15-5.62; p=0.021), TNM stage III&IV (HR=3.79; 95%CI=1.62-8.87; p=0.002) and treatment (HR=0.32; 95%CI=0.21-0.49; p<0.004). Conclusion: Oral cancer patients' survival in HUSM is very low. Older age at diagnosis, loss of weight, present of pain, present of earache, and advanced TNM stage were more likely to die due to oral cancer, while being female and received treatment, were protective factors. All these factors were considerably similar to other countries. Key word: Oral cancer, survival, prognosis, prognostic factors, HUSM.